Assessment of correlation between urinary secretary IgA (sIgA) levels and different types of urinary tract infection (UTI) in various age groups - Navidinia, Masoumeh; Teymouri, Amir Rasoul; Goudarzi, Mehdi (Archives of Advances in Biosciences, 2018)
Urinary tract infections (UTIs) currently rank among the most prevalent infectious diseases worldwide, with chronic and recurrent infections being especially problematic. Urinary secretory IgA (sIgA) in mucosal surface is an important immunological defense in preventing bacterial adherence to periurethral epithelia and uroepithelial. This is a thematic review describing and focusing on a central element which is taken into consideration from different point of views .So, the present study surveyed a brief consideration of assessment correlation between urinary sIgA levels and urinary tract infection (UTI) in various age groups. In children with anatomic abnormalities, higher rates of sIgA was seen compared to children without anatomic abnormalities. The interesting point was that children with recurrent UTI with normal urinary tract had lower levels of sIgA compared to the control group. Also, no remarkable difference of the sIgA concentration rate was seen in healthy and rUTI children who had no bacteriuria; yet, it was considerably higher in children with bacteriuria. It was proven that locally synthesized sIgA was low in patients’ urine with recurrent UTI, independent of the presence or absence of bacteriuria. UTI did not interfere with sIgA secretion as shown by high sIgA in patients with upper UTI. Low urinary sIgA may illustrate one factor predisposing to recurrent UTI. The outcomes displayed that the existence of sIgA is associated with the UTI in children as well as in adults; however, sIgA showed to be manipulative to the infective agent and can also be applied to recognize infection type. Therefore, evaluation of urine antibody levels can provide another marker of host responses to infection, which can be used either as a simple screening test or could be beneficial to facilitate along with other experiments in establishing an assessment.